A Study on the Role of Education in Social Changes: The Interplay between Education and Social and Cultural Transformation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education is two-faced, forward-looking and backward, like too many other civil structures. Education in the older context consists of educating a tribe or a community or a culture in the arts, crafts and principles. Education as an instrument of social and cultural transformation has an immense reach. It should be borne in mind that schooling not only imparts information, but also generates talents, interest, behaviors, expectations and values, promotes social and cultural development, and simultaneously increases the social and cultural standard. Education brings in societal shifts and may contribute to multiple types of transformations and changes in culture. In all respects, which can be seen in a human society such as improvements in expectations in beliefs and ways in thought, the improvements in material traditions, concepts, family interactions, political culture , management patterns at the city , state, regional and national level, engagement in social events, improvements in personal skills and behaviors.In the words of Golda Meyer, schooling is intended to civilize the thousands of barbarians who are born every hour in the world. If schooling does not improve the learner, it is meaningless. Training is the most important weapon to bring about human transformation. Education, on the one side, acculturates an individual on the other, it protects, transmits and develops society 's culture. In brief, schooling and culture in both of their ways and practices are mutually interdependent, compatible and compatible.The scientific growth, the product of schooling, made citizens improve their way of life. Machines are gradually taking over the mechanical functions of men. Now he has more time for fun. There is a huge proliferation in creative talents. The behaviors and preparation of scientists liberate the Indian from his stagnant history of the tradition of dogma, superstitions, rigidity and filled cultural principles and behavioral habits. Today the Indian consciousness holds the technical and science truths of others not just in its ethnic and cultural memories.